1993
DOI: 10.1259/0007-1285-66-788-734
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of a bilobed gallbladder

Abstract: Imaging of the gallbladder demonstrates a wide range of anatomical variants, including anomalies in location, number and shape. Duplication anomalies are quite rare and are characterized by a large variety of configurations depending on the size and degree of fusion of the two lobes, and on the number and disposition of the cystic ducts. We present a case of a deeply cleft, bilobed gallbladder imaged by computed tomography (CT), ultrasonography (US) and oral cholecystography (OCG). The anomaly consisted of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…In humans, septate gallbladder is a congenital malformation that has been described in humans as rare, 46 but some studies consider it common and rarely reported because it is asymptomatic. 47 Despite being harmless, septum may facilitate the formation of gallstones and cause gallbladder blockage, therefore surgical removal is recommended in humans. Indeed, one study reported a relatively high incidence of gallstones associated with septate gallbladder in adult marmosets (Callithrix sp.).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, septate gallbladder is a congenital malformation that has been described in humans as rare, 46 but some studies consider it common and rarely reported because it is asymptomatic. 47 Despite being harmless, septum may facilitate the formation of gallstones and cause gallbladder blockage, therefore surgical removal is recommended in humans. Indeed, one study reported a relatively high incidence of gallstones associated with septate gallbladder in adult marmosets (Callithrix sp.).…”
Section: Discussionmentioning
confidence: 99%
“…Zur Begründung wies er darauf hin, dass viele Angehörige es als Trost empfänden, dass der traurige Tod ihres Nächsten einem anderen Kranken helfen konnte. 320 Martinoli ging laut NZZ soweit, dass er die Angehörigen nach der Transplantation immer wieder über den Gesundheitszustand des Organempfängers informierte. 321 Eine derartige Strategie ist aber ambivalent: Die Fixierung auf das Schicksal des Empfängers kann gefährlich sein, da ein allfälliges Versagen des Transplantats und der Tod des Empfängers die Motive des Helfens und des Weiterlebens grundsätzlich unterlaufen.…”
Section: Das Trostprinzipunclassified
“…They arise from abnormalities in embryogenesis during the fifth and sixth weeks of gestation Causey et al, (2010) and the described malformations vary anatomically in location (site), number, size, shape and heteropias Martinoli et al, (1993); Patel et al, (2008). Boyden (1926), Gross (1936) and Harlaftis et al, (1977) have proposed various types of classifications of congenital malformations of gallbladder based on its anatomic or embryologic development.…”
Section: Introductionmentioning
confidence: 99%
“…Milot et al, (2005) also encountered double gallbladder in a patient with similar pain. The bilobed gallbladder has been encountered in higher vertebrates such as cats with an incidence rate of 10% (Martinoli et al, 1993). Domestic species other than cats have a lower incidence of gallbladder anomalies related to their anatomical differences (Boyden, 1926).…”
Section: Introductionmentioning
confidence: 99%